How Does Farmers’ Digital Literacy Affect Green Grain Production? - Wenqi Wang; Meng Zhang (Agriculture)
Grain production is crucial for national security and stability. Studying the impact of digital literacy on green production by grain farmers is of great significance for ensuring food security and achieving green agricultural development. This article utilizes data from the 2020 China Rural Revitalization Survey (CRRS), selecting a sample of 1811 farming households engaged in grain cultivation. Employing methods such as the ordered Probit model and mediating effect model, it analyzes the impact of digital literacy on green grain production from the perspectives of transformation drivers and pathways. The results show, first, that digital literacy significantly promotes farmers’ green production behaviors, and the findings remain valid after multiple robustness tests. Second, a mechanism analysis reveals that digital literacy drives farmers’ green production by reconstructing their benefit cognition and green cognition and promoting the application of green mechanization technologies. Third, a heterogeneity analysis indicates that the larger the farmers’ operation scale and the stronger their economic capacity, the more significant the promoting effect of digital literacy on their green production. Accordingly, it is necessary to accelerate the improvement of farmers’ digital literacy, reduce green production costs, popularize green mechanization technologies, and promote the green transformation of grain production.